Aptamer CaCO3 Nanostructures: A Facile, pH‐Responsive, Specific Platform for Targeted Anticancer Theranostics. Issue 1 (6th November 2014) - Zhou, Cuisong; Chen, Tao; Wu, Cuichen; Zhu, Guizhi; Qiu, Liping; Cui, Cheng; Hou, Weijia; Tan, Weihong
Abstract The application of cancer theranostics depends on the development of multifunctional nanostructured platforms for accurate cell targeting and controlled drug release, imaging, and therapy. Herein, a comprehensive, easily fabricated anticancer theranostic platform with a high drug‐loading capacity, termed an aptamer‐functionalized calcium carbonate (CaCO3) nanostructure (apt‐CCN), is reported. Flow cytometry and confocal fluorescence microscopy studies demonstrate that apt‐CCNs can specifically bind to target cancer cells, but not to control cells, and that they possess highly efficient internalization to target cancer cells. This smart nanostructure selectively reaches the lysosomes through receptor‐mediated endocytosis and is responsive to the relatively low lysosome pH (4.5–5.5), which facilitates the release of doxorubicin. The apt‐CCN platform offers targeted and efficient drug transport, as well as target‐specific delivery of imaging agents for cancer diagnosis and therapy.